2007
DOI: 10.1254/jphs.cr0070024
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-Catenin Signaling Pathway as a Target in Drug Discovery

Abstract: Abstract. The cell signaling cascades provoked by Wnt proteins (the Wnt signaling pathways), which are well conserved through evolution, play crucial roles to maintain homeostasis of a variety of tissues such as skin, blood, intestine, and brain, as well as to regulate proliferation, morphology, motility, and fate of cells during embryonic development. Among these pathways, the signal transduction through β-catenin (the Wnt / β-catenin signaling pathway) has been most intensively studied because this signal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 100 publications
2
84
0
7
Order By: Relevance
“…15,16 In our previous study, we demonstrated that b-catenin-targeting cancer therapy was effective in inhibiting tumor cell growth. 4 However, suppression of b-catenin may cause unexpected changes in the pathophysiology of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In our previous study, we demonstrated that b-catenin-targeting cancer therapy was effective in inhibiting tumor cell growth. 4 However, suppression of b-catenin may cause unexpected changes in the pathophysiology of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to phosphorylation by GSK3β, priming phosphorylation of serine 45 on β-catenin by casein kinase 1 (CK1) is required, where CK1 is bound to axin [8]. Concurrently, transcriptional activity of TCF is inhibited by corepressor Groucho [9]. Upon binding of the Wnt ligand to the FZD membrane receptor protein and low-density lipoprotein receptor-related proteins (LRP-5/6), the canonical Wnt signalling pathway is activated ( Figure 1).…”
Section: Canonical Wnt Signalling Pathwaymentioning
confidence: 99%
“…As a specific example, several cancers, including the majority of colon adenocarcinomas, arise due to gain-offunction mutations in the canonical Wnt signaling pathway. Pharmacological inhibitors of Wnt pathway are being actively developed in cancer medicine and it is possible that these may also find a role in enhancing remyelination by inhibiting Wnt signaling in CNS precursors and normalizing the kinetics of myelin regeneration [81,82].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%